INNOVATION ADOPTION BARRIERS IN INDONESIAN MANUFACTURING SMALL AND MEDIUM ENTERPRISES - Herry Achmad Buchory; Uce Karna Suganda; Ijang Faisal (Journal of Economics, Accounting, Business, Management, Engineering and Society, 2024)
Background: Innovation adoption remains critical for manufacturing SME competitiveness, yet many Indonesian enterprises struggle to implement innovations despite recognizing their importance. Aims: This study identifies and analyzes primary barriers preventing Indonesian manufacturing SMEs from successfully adopting innovations. Research Method: Qualitative approach involving in-depth interviews with 32 manufacturing SME owners and managers across West Java representing diverse subsectors. Thematic analysis identified recurring barrier patterns. Results and Conclusion: Analysis reveals five major barrier categories: financial resource constraints (78%), technical knowledge gaps (65%), organizational risk aversion (58%), infrastructure limitations (52%), and regulatory complexity (43%). Barriers interact creating compound effects. Contribution: Research provides empirical evidence on innovation barriers in Indonesian manufacturing SME contexts, offering practical recommendations for targeted interventions.